Changes in Oxidative Stress-Related Biomarkers May Have a Role in The Pathophysiological Mechanisms Involved in Autism - Abd El-Hamid, Shadia; Sherif, Naglaa Mostafa; Ezz-eldine, Nermine (Arab Journal for Sciences and Research Publishing, 2015)
There is evidence that oxygen free radicals play a vital part in the pathophysiology of numerous neuropsychiatric disorders. Although it has not been investigated yet, several recent studies proposed that nitric oxide (NO) and other parameters related to oxidative stress may have a pathophysiological role in autism. This study aims to evaluate the plasma levels of antioxidant enzyme, superoxide dismutase (SOD) and plasma level of Nitric oxide(NO), a marker of oxidative stress, in Egyptian autistic children. Autism is a neurodevelopmental disorder of childhood with poorly understood etiology and pathology. The present study included 40 children with autism diagnosed by DSM-V-TR criteria and Childhood Autism Rating Scale. Controls included 40 age-matched healthy children.Cases were referred to Outpatient Clinic of Children with Special Needs Department, National Research Center, Cairo, Egypt. We compared levels of SOD, and NO in children with autism and controls. Level of NO was significantly higher in autistic children compared with their controls, while SOD was significantly lower among patients than controls. These findings indicate a possible role of increased oxidative stress and altered enzymatic antioxidants, both of which may be relevant to the pathophysiology of autism.
Keywords: Autism Spectrum disorder; Nitric oxide; reactive oxygen species; Oxidative stress